Perbandingan Model PBL dengan Model Blended Learning terhadap Hasil Belajar Siswa Kelas IX Mata Pelajaran Agama Islam di SMP - Ilyas Reski Aziz (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Islamic Religious Education (PAI) learning at the junior high school level still faces various challenges, especially related to low learning outcomes and the lack of active student involvement in the learning process. This is largely due to the conventional approach that is still widely used by teachers. To overcome these problems, an innovative learning model is needed that is able to increase student participation and understanding. This study compares the effectiveness of the Problem Based Learning model and Blended Learning in Islamic Religious Education learning. The experimental method was used with a posttest-only control group design on grade IX students of SMP Negeri 3 Panyabungan. Data were obtained through essay tests and analyzed using t-tests. The results showed that the PBL model produced higher learning scores than Blended Learning. These findings indicate that PBL is more effective in improving student learning outcomes in the context of PAI subjects.